Separation Methods of the Eggshell Membranes from Eggshell - Diana Pasarin; Camelia Rovinaru (Proceedings, 2019)
As a result of the technological processes of the egg industry, there are tons of egg shells, which raise environmental problems and costs for their management. [...]